(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Pancasila, as the foundation of the Indonesian state, provides moral guidelines and universal values such as divinity, humanity, unity, democracy, and justice for its people. Teenagers as the nation’s next generation have an important role in determining the direction of the nation, but their ethics and morality are increasingly moving away from the values of Pancasila. This research uses qualitative methods to describe the implementation of Pancasila values in the morals and ethics of students and the factors that influence them. Various parties such as the government, educational institutions, families, and society have roles and responsibilities in increasing the implementation of Pancasila values. The strategies needed include socialization through education and social media as well as the formation of Pancasila attitudes in schools through Citizenship Education teachers. By collaborating with all parties and implementing an integrated strategy, it is hoped that the younger generation can understand and internalize the values of Pancasila.